This house believes that sulphonylureas should not be used routinely as second-line treatments for patients with type 2 diabetes - Ryder, R; Holman, R; Gwilt, M (Association of British Clinical Diabetologists, 2016)
Sulphonylureas (SU) have received a terrible press in recent years. A series of publications over many years have told us that SUs increase the risk of adverse cardiovascular outcomes in diabetes patients (usually relative to metformin in observational studies),1 analyses from ACCORD and other mega trials have heightened concern over severe hypoglycaemia as a risk factor for premature mortality2 and it is not uncommon to hear that SUs induce β-cell exhaustion.3 The place of metformin (with lifestyle intervention) looks secure at the head of the management algorithm for type 2 diabetes, for the time being at least.4,5 But most type 2 diabetes patients will need the addition of a second pharmacological agent to their regimen at some point, as their β-cell function continues to wane. Is it time we finally said goodbye to SUs as a second-line management option with metformin, or have their limitations been overstated? Two distinguished diabetologists and clinical trialists, Professor Rury R Holman and Dr Robert EJ Ryder, went head-to-head recently to address this important question.